Anti-Cancer Activity of Lobaric Acid and Lobarstin Extracted from the Antarctic Lichen Stereocaulon alpnum - Ju-Mi Hong; Sung-Suk Suh; Tai Kim; Jung Kim; Se Han; Ui Youn; Joung Yim; Il-Chan Kim (Molecules, 2018)
Lobaric acid and lobarstin, secondary metabolites derived from the antarctic lichen Stereocaulon alpnum, exert various biological activities, including antitumor, anti-proliferation, anti-inflammation, and antioxidant activities. However, the underlying mechanisms of these effects have not yet been elucidated in human cervix adenocarcinoma and human colon carcinoma. In the present study, we evaluated the anticancer effects of lobaric acid and lobarstin on human cervix adenocarcinoma HeLa cells and colon carcinoma HCT116 cells. We show that the proliferation of Hela and HCT116 cells treated with lobaric acid and lobarstin significantly decreased in a dose- and time-dependent manner. Using flow cytometry analysis, we observed that the treatment with these compounds resulted in significant apoptosis in both cell lines, following cell cycle perturbation and arrest in G2/M phase. Furthermore, using immunoblot analysis, we investigated the expression of cell cycle and apoptosis-related marker genes and found a significant downregulation of the apoptosis regulator B-cell lymphoma 2 (Bcl-2) and upregulation of the cleaved form of the poly (ADP-ribose) polymerase (PARP), a DNA repair and apoptosis regulator. These results suggest that lobaric acid and lobarstin could significantly inhibit cell proliferation through cell cycle arrest and induction of apoptosis via the mitochondrial apoptotic pathway in cervix adenocarcinoma and colon carcinoma cells. Taken together, our data suggests that lobaric acid and lobarstin might be novel agents for clinical treatment of cervix adenocarcinoma and colon carcinoma.